Implementation of pencil beam redefinition algorithm (PBRA) for intraoperative electron radiation therapy (IOERT) treatment planning. (December 2022) - Tavallaie, Mina; Hariri Tabrizi, Sanaz; Heidarloo, Nematollah
Highlights: Pencil Beam Redefination Algorithm (PBRA) was implemented with three initialization methods and compared to MC. Phase space distribution of the electrons below the applicator was generated using MC simulation. The agreement between PBRA dose calculation and MC is promising for development of an intraoperative TPS for IOERT. Abstract: Purpose: Similar to other radiation therapy techniques, intraoperative electron radiation therapy (IOERT) can benefit from an online treatment planning system (TPS). Among all the analytical electron dose calculation algorithms, pencil beam redefinition algorithm (PBRA) has shown an acceptable accuracy in inhomogeneities. The input dataset for PBRA includes electron planar fluence, mean direction and root mean square (RMS) spread about the mean direction which had been introduced based on the conventional linear accelerator geometry in former studies. Herein, three methods for implementing PBRA for IOERT system are presented. Methods: The initialization parameters were identified using Monte Carlo (MC) simulation of a dedicated IOERT system equipped with a cylindrical 10 cm applicator, irradiating a water phantom. Phase space distribution of electrons was recorded on a plane below the applicator. The input dataset was extracted for 2 × 2 mm 2 pixels and energy bin width of 1 MeV. Results: PBRA was implemented with three initialization methods and compared to MC. The 3D gamma analysis of the algorithm with the Formula method, which was in best agreement with MC in a simple water phantom, showed passing rates of more than 99 % for all nominal energies and it was 97.1 % for 8 MeV in the presence of protecting disk and irregular surface. Implementing PBRA on CUDA C++ resulted in 5 s run time for 8 MeV nominal energy in a water phantom. Conclusions: The agreement between PBRA dose calculation and MC is promising for the development of an intraoperative TPS for IOERT.